A reinforced halogen-free flame-retardant battery shell material and preparation method

By using the combination of hyperbranched flame retardant graft modified zirconium phosphate and ABS resin in the lead-acid battery housing material, the problem of insufficient flame retardant is solved, and a battery housing material with high toughness and good flame retardant performance is achieved, ensuring that Improved safety and performance.

CN117487308BActive Publication Date: 2024-12-20YANTAI GRACE POLYMER MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311655551.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2024-12-20
Estimated Expiration
2043-12-05

AI Technical Summary

Technical Problem

The flame retardancy of the lead-acid battery housing material is insufficient and cannot provide safety guarantees. The addition of flame retardant will reduce the mechanical properties and weather resistance of the material.

Method used

Hyperbranched flame retardant graft modified zirconium phosphate is prepared through specific synthesis steps, combining ABS matrix resin, antioxidants, light stabilizers and processing aids to form high toughness and good flame retardant properties. Battery housing material.

Benefits of technology

The V-0-level flame retardant performance of the material is achieved, the mechanical properties and toughness are improved, the safety and service life of the battery case are ensured, and the performance of the flame retardant is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a reinforced halogen-free flame-retardant battery shell material and a preparation method, which belongs to the technical field of battery shell materials, and includes the following raw materials by weight: 78-84 parts of ABS matrix resin, 14-16 parts of flame retardant, 0.2-0.3 parts of antioxidant, 0.8-0.9 parts of light stabilizer, and 0.8-0.9 parts of processing aid; the flame retardant is hyperbranched flame-retardant grafted modified zirconium phosphate. After weighing the antioxidant and the light stabilizer according to the formula and mixing them evenly, the flame retardant, the processing aid and the ABS matrix resin are added, and premixed in a mixer, the premix is ​​put into a twin-screw extruder, extruded and granulated, and the prepared flame-retardant plastic particles are dried and injection molded; the invention makes the flame retardant grade of the material reach V-0 level by adding halogen-free flame retardant hyperbranched flame-retardant grafted modified zirconium phosphate, and the addition of the flame retardant not only does not reduce the mechanical properties of the material, but improves the mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery shell material preparation, and in particular relates to a reinforced halogen-free flame-retardant battery shell material and a preparation method thereof. Background Art

[0002] The main components of lead-acid batteries are: battery shell, positive and negative plates, and separators. Whether the selection of the battery shell is reasonable directly affects the performance of the battery. There are certain requirements for the shell material of lead-acid batteries, such as:

[0003] It has good flame retardancy and provides safety protection for power battery packs that require strong flame retardancy. It has sufficient mechanical strength to withstand vibration, impact, overload, and impact resistance under conditions such as ground storage, transportation, and alternating temperature. It has certain chemical stability and its performance should be well maintained in sulfuric acid electrolyte for a long time. It has a wide temperature range (-40~60℃) and a long service life. It has good electrical insulation to prevent leakage during battery use. It has good air and liquid impermeability, etc.

[0004] ABS resin material is a terpolymer composed of acrylonitrile, butadiene and styrene, with excellent physical and mechanical properties: high impact strength in a fairly wide temperature range, high surface hardness, good compression, tension and bending resistance; excellent wear resistance, chemical resistance and electrical properties; high heat deformation temperature, good product dimensional stability, and easy processing and molding; ABS resin material is a better choice for lead-acid battery shell material, but ABS resin is a flammable material and cannot provide safety guarantees. The solution of adding flame retardants to achieve flame retardant effects will deteriorate the mechanical properties, heat resistance and weather resistance of ABS resin materials to varying degrees. Summary of the invention

[0005] The object of the present invention is to provide a reinforced halogen-free flame-retardant battery casing material and a preparation method thereof, so as to solve the problem that the battery casing material has insufficient flame retardancy and cannot provide safety assurance.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A reinforced halogen-free flame-retardant battery shell material, comprising the following raw materials in parts by weight:

[0008] 78-84 parts of ABS matrix resin, 14-16 parts of flame retardant, 0.2-0.3 parts of antioxidant, 0.8-0.9 parts of light stabilizer and 0.8-0.9 parts of processing aid; the flame retardant is hyperbranched flame retardant grafted modified zirconium phosphate.

[0009] Furthermore, the hyperbranched flame retardant grafted modified zirconium phosphate is prepared by the following steps:

[0010] Epoxidized zirconium phosphate, amino-terminated hyperbranched flame retardant modifier and triethylamine were added to N,N-dimethylformamide, heated and refluxed for 6 hours under nitrogen protection, cooled after the reaction, washed with anhydrous ethanol, and dried to obtain a branched modified solid. The branched modified solid was added to chloroform, stirred and dispersed, triethylamine and octanoyl chloride were added, stirred and reacted for 6 hours, and hyperbranched flame retardant grafted modified zirconium phosphate was obtained after sedimentation, suction filtration and drying; the mass ratio of epoxidized zirconium phosphate, amino-terminated hyperbranched flame retardant modifier and triethylamine was 1:2:1. The addition of octanoyl chloride can consume part of the amino groups in the hyperbranched flame retardant grafted modified zirconium phosphate, further enhance the bonding force between the flame retardant and the resin, promote the dispersion of the flame retardant, and jointly improve the toughness of the material.

[0011] Furthermore, the epoxidized zirconium phosphate is prepared by the following steps:

[0012] Add nano zirconium phosphate into water and disperse it ultrasonically, add glacial acetic acid dropwise, control the mass ratio of nano zirconium phosphate, acetic acid and water to be 4:1:200, and after stirring and dispersing, add γ-glycidyloxypropyltrimethoxysilane ethanol solution (γ-glycidyloxypropyltrimethoxysilane and ethanol in a mass ratio of 1:20), stir and disperse for 30 minutes at 30°C, then raise the temperature to 65°C and continue the reaction for 1 hour. After the reaction is completed, settle, filter and dry to obtain epoxidized zirconium phosphate.

[0013] Nano zirconium phosphate is synthesized by hydrothermal method, ZrOCl2·8H2O and water are mixed, stirred and dispersed, a certain amount of concentrated phosphoric acid is added dropwise under stirring to form a gel solution, and the acidity of the system is adjusted to pH < 1. The gel solution is transferred into a reaction kettle and placed in a constant temperature oven, taken out after drying, and naturally cooled to room temperature. The product is fully washed with distilled water to pH ≥ 5, and vacuum dried at 60°C.

[0014] Furthermore, the amino-terminated hyperbranched flame retardant modifier is prepared by the following steps:

[0015] Under nitrogen protection, anhydrous toluene, hexachlorocyclotriphosphazene and diamine monomer are mixed, and triethylamine is added after stirring and dissolving. The temperature is raised to 70°C and stirred for reaction for 10-12 hours. The reaction is concentrated under reduced pressure to remove the solvent to obtain an amino-terminated hyperbranched flame retardant modifier; the molar ratio of hexachlorocyclotriphosphazene to diamine monomer is 6:1. The amino-terminated hyperbranched flame retardant modifier has high phosphorus and high nitrogen. Combined with zirconium phosphate, the flame retardant effect of the flame retardant is synergistically improved through the combination of organic and inorganic, promoting carbonization and blocking heat transfer. In addition, the branched structure of the amino-terminated hyperbranched flame retardant modifier has a good dispersion effect, and it has excellent dispersibility and low viscosity, better processing characteristics, and good adaptability in raw materials.

[0016] Furthermore, the diamine monomer includes 4,4'-diaminodiphenylmethane, p-phenylenediamine and ethylenediamine.

[0017] Furthermore, the antioxidant is antioxidant 1010 or antioxidant 168.

[0018] Furthermore, the light stabilizer is one or a mixture of 2-hydroxybenzophenone, diphenyl phosphite, triphenyl phosphite, and hydroxybenzotriazole.

[0019] Furthermore, the processing aid includes one or a mixture of several of ethylene bisstearamide, silicone oil and white mineral oil.

[0020] Furthermore, it is characterized by comprising the following steps:

[0021] After weighing antioxidant and light stabilizer according to the formula and mixing evenly, add flame retardant, processing aid and ABS matrix resin, premix in a mixer, put the premix into a twin-screw extruder, extrude granulation, and after drying the prepared flame-retardant plastic particles, injection molding is performed to obtain a reinforced halogen-free flame-retardant battery shell material.

[0022] Furthermore, it is characterized in that the temperature of the twin-screw extruder barrel is controlled in 10 sections, and the temperature is 180-210°C; the injection molding temperature range is 180-210°C.

[0023] Beneficial effects of the present invention:

[0024] The present invention provides a reinforced halogen-free flame-retardant battery shell material, which can achieve a flame retardant grade of V-0 by adding a halogen-free flame retardant hyperbranched flame-retardant grafted modified zirconium phosphate, meet the flame retardant requirements, and the addition of the flame retardant will not only not reduce the mechanical properties of the material, but improve the mechanical properties. The prepared battery shell material has high toughness and high notch impact strength.

[0025] The flame retardant-free particles in the present invention are a kind of reinforced particles, the core of which is zirconium phosphate, and the outer layer is wrapped with a layer of terminal amino hyperbranched flame retardant modifier, forming a "soft outside and hard inside" particle with a unique structure; wherein the existence of the flexible interface layer can eliminate the residual stress of the material by deformation, absorb a certain amount of external energy, and improve the toughness of the material. Zirconium phosphate has a lamellar structure, and within a certain range of addition, the addition will increase the bending strength of the material, but zirconium phosphate is a rigid particle. Too much addition will cause a decrease in toughness, so the mechanical properties of untreated zirconium phosphate are significantly reduced compared to the material. Conventional silane coupling agent treatment improves the dispersion of zirconium phosphate in the raw material, but as the addition amount increases, the effect will be less obvious.

[0026] The flame retardant in the present invention is a halogen-free flame retardant and is more environmentally friendly. As a reinforcing particle, the components constituting the flame retardant have a good flame retardant synergistic effect, which not only makes the battery shell material have good flame retardant properties, but also improves the toughness of the battery shell material and increases its impact strength. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0028] This embodiment provides a terminal amino hyperbranched flame retardant modifier, which is prepared by the following steps:

[0029] Under nitrogen protection, anhydrous toluene, hexachlorocyclotriphosphazene and 4,4'-diaminodiphenylmethane were mixed, stirred and dissolved, and triethylamine was added. The temperature was raised to 70°C and stirred for 2 hours. The reaction was concentrated under reduced pressure to remove the solvent to obtain an amino-terminated hyperbranched flame retardant modifier. The molar ratio of hexachlorocyclotriphosphazene to diamine monomer was 6:1. Toluene was used as a solvent, and the total mass of hexachlorocyclotriphosphazene and 4,4'-diaminodiphenylmethane and anhydrous toluene was 1g:10mL. Example 2

[0030] This embodiment provides a terminal amino hyperbranched flame retardant modifier, which is prepared by the following steps:

[0031] Under nitrogen protection, anhydrous toluene, hexachlorocyclotriphosphazene and p-phenylenediamine were mixed, stirred and dissolved, and triethylamine was added, and the temperature was raised to 70°C and stirred for 11 hours. The reaction was concentrated under reduced pressure to remove the solvent to obtain an amino-terminated hyperbranched flame retardant modifier. The molar ratio of hexachlorocyclotriphosphazene to diamine monomer was 6:1. Toluene was used as a solvent, and the total mass of hexachlorocyclotriphosphazene and p-phenylenediamine and anhydrous toluene was 1g:10mL. Example 3

[0032] This embodiment provides a terminal amino hyperbranched flame retardant modifier, which is prepared by the following steps:

[0033] Under nitrogen protection, anhydrous toluene, hexachlorocyclotriphosphazene and ethylenediamine were mixed, stirred and dissolved, and triethylamine was added, the temperature was raised to 70°C and stirred for 10 hours, and the reaction was concentrated under reduced pressure to remove the solvent to obtain an amino-terminated hyperbranched flame retardant modifier. The molar ratio of hexachlorocyclotriphosphazene to diamine monomer was 6:1. Toluene was used as a solvent, and the total mass of hexachlorocyclotriphosphazene and ethylenediamine and anhydrous toluene were used in a ratio of 1g:10mL. Example 4

[0034] This embodiment provides a hyperbranched flame retardant grafted modified zirconium phosphate, which is prepared by the following steps:

[0035] Nano zirconium phosphate was added to water for ultrasonic dispersion, and glacial acetic acid was added dropwise, and the mass ratio of nano zirconium phosphate, acetic acid and water was controlled to be 4:1:200. After stirring and dispersion, γ-glycidyloxypropyltrimethoxysilane ethanol solution (γ-glycidyloxypropyltrimethoxysilane and ethanol were in a mass ratio of 1:20) was added dropwise, and the mixture was stirred and dispersed for 30 minutes at a temperature of 30°C, and then the temperature was raised to 65°C for continued reaction for 1 hour. After the reaction was completed, the mixture was settled, filtered and dried to obtain epoxidized zirconium phosphate. Nano zirconium phosphate was synthesized by hydrothermal method, and ZrOCl2·8H2O and water were mixed, stirred and dispersed, and a certain amount of concentrated phosphoric acid was added dropwise under stirring to form a gel solution, and the acidity of the system was adjusted to pH <1. The gel solution was transferred to a reactor and placed in a constant temperature oven, taken out after drying, and naturally cooled to room temperature. The product was fully washed with distilled water until pH ≥ 5, and vacuum dried at 60°C.

[0036] 20g of epoxidized zirconium phosphate, 40g of the amino-terminated hyperbranched flame retardant modifier prepared according to the proportion in Example 1 and 20g of triethylamine were added to 1.5L of N,N-dimethylformamide, and the mixture was heated and refluxed for 6h under nitrogen protection. After the reaction was completed, the mixture was cooled, washed with anhydrous ethanol, and dried to obtain a branched modified solid. 40g of the branched modified solid was added to 2L of chloroform, stirred and dispersed, 20g of triethylamine and 25g of octanoyl chloride were added, stirred and reacted for 6h, and the hyperbranched flame retardant grafted modified zirconium phosphate was obtained after sedimentation, suction filtration, and drying. Example 5

[0037] In this example, the amino-terminated hyperbranched flame retardant modifier was replaced with a sample prepared according to the proportion in Example 2, and the remaining raw materials and preparation process remained the same as in Example 4. Example 6

[0038] In this example, the amino-terminated hyperbranched flame retardant modifier was replaced with a sample prepared according to the proportions in Example 3, and the remaining raw materials and preparation process remained the same as in Example 4.

[0039] Preparation of test samples: Example 7

[0040] A method for preparing a reinforced halogen-free flame-retardant battery casing material comprises the following steps:

[0041] According to weight, 0.3 parts of antioxidant 1010 and 0.9 parts of 2-hydroxybenzophenone were weighed and mixed evenly, and then 16 parts of hyperbranched flame retardant grafted modified zirconium phosphate obtained in Example 4, 0.9 parts of white mineral oil and 84 parts of ABS matrix resin were added and premixed in a high-speed mixer, wherein the ABS matrix resin was ABS D-120A and ABS AG15A1 compounded according to a mass ratio of 5:1; the premix was put into a twin-screw extruder, and the temperature of the twin-screw extruder barrel was controlled in 10 sections, and the temperature was controlled in the range of 180-210°C. The main engine speed was 1020r / min, the feeding speed was 400r / min, and extrusion granulation was performed, and the prepared flame retardant plastic particles were dried at 80°C for 4h, and injection molding was performed to obtain a reinforced halogen-free flame retardant battery shell material, and the injection molding temperature range was 180-210°C. Example 8

[0042] A method for preparing a reinforced halogen-free flame-retardant battery casing material comprises the following steps:

[0043] According to weight, 0.3 parts of antioxidant 1010 and 0.9 parts of 2-hydroxybenzophenone were weighed and mixed evenly, and then 15 parts of hyperbranched flame retardant grafted modified zirconium phosphate obtained in Example 5, 0.9 parts of white mineral oil and 82 parts of ABS matrix resin were added and premixed in a high-speed mixer, wherein the ABS matrix resin was ABS D-120A and ABS AG15A1 compounded according to a mass ratio of 5:1; the premix was put into a twin-screw extruder, and the temperature of the twin-screw extruder barrel was controlled in 10 sections, and the temperature was controlled in the range of 180-210°C. The main engine speed was 1020r / min, the feeding speed was 400r / min, and extrusion granulation was performed, and the prepared flame retardant plastic particles were dried at 80°C for 4h, and injection molding was performed to obtain a reinforced halogen-free flame retardant battery shell material, and the injection molding temperature range was 180-210°C. Example 9

[0044] A method for preparing a reinforced halogen-free flame-retardant battery casing material comprises the following steps:

[0045] According to weight, 0.2 parts of antioxidant 1010 and 0.8 parts of 2-hydroxybenzophenone were weighed and mixed evenly, and then 14 parts of hyperbranched flame retardant grafted modified zirconium phosphate obtained in Example 6, 0.8 parts of white mineral oil and 78 parts of ABS matrix resin were added and premixed in a high-speed mixer, wherein the ABS matrix resin was ABS D-120A and ABS AG15A1 compounded according to a mass ratio of 5:1; the premix was put into a twin-screw extruder, and the barrel temperature of the twin-screw extruder was controlled in 10 sections, the temperature was controlled in the range of 180-210°C, the main engine speed was 1020r / min, the feeding speed was 400r / min, extrusion granulation was performed, and the prepared flame retardant plastic particles were dried at 80°C for 4h, and injection molding was performed to obtain a reinforced halogen-free flame retardant battery shell material, and the injection molding temperature range was 180-210°C.

[0046] Comparative Example 1

[0047] Compared with Example 7, this comparative example replaces the hyperbranched flame retardant grafted modified zirconium phosphate with the epoxidized zirconium phosphate in Example 4, and the remaining raw materials and preparation process remain the same as those in Example 7.

[0048] Comparative Example 2

[0049] Compared with Example 7, this comparative example replaces the hyperbranched flame retardant grafted modified zirconium phosphate with untreated zirconium phosphate, and the other raw materials and preparation process remain the same as those in Example 7.

[0050] Comparative Example 3

[0051] No flame retardant was added, and the remaining raw materials and preparation process remained the same as in Example 7.

[0052] Performance Test:

[0053] Izod notched impact strength is measured according to GB / T1843-2008;

[0054] Bending properties are measured according to GB / T9341-2008;

[0055] Tensile properties are measured according to GB / T1040-2018;

[0056] Vertical burning performance is measured according to UL94;

[0057] The Vicat softening temperature is determined according to ASTM D1525-2017; the heat deformation temperature is determined according to ASTM D648 plastic heat deformation temperature test method;

[0058] Performance tests were performed on Examples 7 to 9 and Comparative Examples 1 to 2, and the results are shown in Table 1:

[0059] Figure 1

[0060] ;

[0061] It can be seen from Table 1 that the material prepared by the present invention can still maintain good toughness (high Izod notched impact strength) under normal temperature or low temperature test conditions, and the mechanical properties of the material will not be reduced due to the addition of the flame retardant system, and has good flame retardant properties.

[0062] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A reinforced halogen-free flame-retardant battery casing material, characterized in that: The composition comprises the following raw materials in parts by weight: 78-84 parts of ABS matrix resin, 14-16 parts of flame retardant, 0.2-0.3 parts of antioxidant, 0.8-0.9 parts of light stabilizer, and 0.8-0.9 parts of processing aid; the flame retardant is hyperbranched flame retardant grafted modified zirconium phosphate; The hyperbranched flame retardant grafted modified zirconium phosphate is prepared by the following steps: Add nano zirconium phosphate into water for ultrasonic dispersion, add glacial acetic acid dropwise, control the mass ratio of nano zirconium phosphate, acetic acid and water to be 4:1:200, stir and disperse, add γ-glycidyloxypropyltrimethoxysilane ethanol solution dropwise, stir and disperse for 30 minutes at 30°C, then heat to 65°C and continue to react for 1 hour, and after the reaction is completed, settle, filter and dry to obtain epoxidized zirconium phosphate; Under nitrogen protection, anhydrous toluene, hexachlorocyclotriphosphazene and diamine monomer are mixed, and triethylamine is added after stirring to dissolve, and the temperature is raised to 70°C and stirred to react for 10-12 hours. The reaction is concentrated under reduced pressure to remove the solvent, and an amino-terminated hyperbranched flame retardant modifier is obtained; the molar ratio of hexachlorocyclotriphosphazene to the diamine monomer is 6:1; Epoxidized zirconium phosphate, amino-terminated hyperbranched flame retardant modifier and triethylamine are added to N,N-dimethylformamide, and the temperature is raised to reflux for reaction for 6 hours under nitrogen protection. After the reaction is completed, the reaction is cooled, washed with anhydrous ethanol, and dried to obtain a branched modified solid. After the branched modified solid is added to chloroform, it is stirred and dispersed, triethylamine and octanoyl chloride are added, and the reaction is stirred for 6 hours. After sedimentation, suction filtration and drying, a hyperbranched flame retardant grafted modified zirconium phosphate is obtained; the mass ratio of epoxidized zirconium phosphate, amino-terminated hyperbranched flame retardant modifier and triethylamine is 1:2:

1.

2. The reinforced halogen-free flame-retardant battery casing material according to claim 1, characterized in that: The diamine monomers include 4,4'-diaminodiphenylmethane, p-phenylenediamine and ethylenediamine.

3. The reinforced halogen-free flame-retardant battery casing material according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 168.

4. The reinforced halogen-free flame-retardant battery casing material according to claim 1, characterized in that: The light stabilizer is one or a mixture of 2-hydroxybenzophenone, diphenyl phosphite, triphenyl phosphite, and hydroxybenzotriazole.

5. The reinforced halogen-free flame-retardant battery casing material according to claim 1, characterized in that: The processing aid comprises one or a mixture of several of ethylene bis stearic acid amide, silicone oil and white mineral oil.

6. The method for preparing a reinforced halogen-free flame-retardant battery casing material according to claim 1, characterized in that: The steps include: After weighing antioxidant and light stabilizer according to the formula and mixing evenly, add flame retardant, processing aid and ABS matrix resin, premix in a mixer, put the premix into a twin-screw extruder, extrude granulation, and after drying the prepared flame-retardant plastic particles, injection molding is performed to obtain a reinforced halogen-free flame-retardant battery shell material.

7. The method for preparing a reinforced halogen-free flame-retardant battery casing material according to claim 6, characterized in that: The twin-screw extruder barrel temperature is controlled in 10 sections, the temperature is 180-210℃; the injection molding temperature range is 180-210℃.

Citation Information

Patent Citations

  • Housing material for halogen-free flame retardant storage battery and preparation method thereof

    CN103183901A

  • Phosphonitrile / triazine double-group molecular flame retardant based on in-situ doping of nanoscale metal compound, and preparation method thereof

    CN106543473A